2000
DOI: 10.1002/1097-0177(2000)9999:9999<::aid-dvdy1045>3.3.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Induction of lef1 during zebrafish fin regeneration

Abstract: Elastin‐like polypeptides (ELPs) are polypentapeptides that undergo hydrophobic collapse and aggregation above a specific transition temperature, Tt. ELP diblocks sharing a common “core” block (I60) but varying “outer” blocks (A80, P40) were designed, where Tt,I < Tt,A < Tt,P. The formation of ∼55 nm diameter mixed micelles from these ELP diblocks was verified using dynamic light scattering (DLS), multiangle light scattering (MALS) and fluorescence resonance energy transfer (FRET). To confer affinity to the bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(116 citation statements)
references
References 31 publications
4
111
0
1
Order By: Relevance
“…miR-203 was found to be significantly downregulated during regeneration and is predicted to target lef1 (Table 1), a Wnt signaling-regulated transcription factor, the transcription of which is induced during regeneration and serves as a marker of the basal epidermal layer during blastema formation (22). The 3Ј UTR of lef1 contains two potential miRNA recognition elements (MREs) for miR-203 ( Fig.…”
Section: Figmentioning
confidence: 84%
See 1 more Smart Citation
“…miR-203 was found to be significantly downregulated during regeneration and is predicted to target lef1 (Table 1), a Wnt signaling-regulated transcription factor, the transcription of which is induced during regeneration and serves as a marker of the basal epidermal layer during blastema formation (22). The 3Ј UTR of lef1 contains two potential miRNA recognition elements (MREs) for miR-203 ( Fig.…”
Section: Figmentioning
confidence: 84%
“…Similarly, miR-203 is down-regulated during regeneration and is predicted to target lef1. Regeneration requires up-regulation of lef1 in newly formed regenerative epithelia and can be used as a marker for the initiation of regeneration (21)(22)(23). Thus, significant downregulation of miR-203 during regeneration is consistent with the up-regulation of lef1 that occurs during active regeneration.…”
Section: Lef1 ͉ Mir-203mentioning
confidence: 99%
“…While amphibians have long been the central characters employed in studies on tissue or organ regeneration (Brockes, 1997;Beck et al, 2009;Contreras et al, 2009;Kragl et al, 2009;Calve et al, 2010), the zebrafish (Danio rerio) have recently emerged as a new vertebrate model for genetic studies of tissue/ organ regeneration. Like amphibians, zebrafish exhibit an enhanced capability of regenerating adult tissues, which include retina, spinal cord, kidney, heart, and fin (Poss et al, 2000a(Poss et al, ,b, 2002aNechiporuk and Keating, 2002;Nechiporuk et al, 2003;Jazwinska et al, 2007;Schoenebeck et al, 2007;Tsai et al, 2007;Qin et al, 2009;Jopling et al, 2010;Thummel et al, 2010). Fin regeneration is a particularly efficient model for studying tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…During fin regeneration, a large number of genes, including signalling molecules and transcription factors, are expressed with the end of restoring loss and damaged parts (Poss et al, 2000a;Nechiporuk and Keating, 2002). Laforest et al (1998) analysed the expression of genes involved in the pathway of signalling SHH (Sonic Hedgehog) and observed that shh, ptc and bmp2 are expressed during the fin regeneration in a coordinated way, suggesting the function of these genes in the interaction epidermisblastema, which leads to the synthesis and to the restoration of the ray.…”
Section: Discussionmentioning
confidence: 99%
“…Fin regeneration is characterised by: formation of a multilayered wound epidermis, disorganisation and distal migration of mesenchymal cells proximal to the amputation plane, proliferation of these mesenchymal cells to form the regeneration blastema, continued distal blastemal proliferation to facilitate outgrowth and proximal blastemal differentiation to replace missing structures (Goss and Stagg, 1957;Santamaria and Becerra, 1991;Johnson and Weston, 1995;Poss et al, 2000aPoss et al, , 2000b.…”
Section: Introductionmentioning
confidence: 99%